Kinerja Sosial Lembaga Perkreditan Desa - Baskara, I Gde Kajeng; Triaryati, Nyoman (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 14 Nomor 2 Tahun 2020DO - 10.24843/MATRIK:JMBK.2020.v14.i02.p05, 2020)
This research aims to measure the social performance of Village Credit Institutions (VCI). VCI performance is not only seen from financial performance, but the social performance has also need to be assessed. The social performance management is measured by four dimension using the Social Performance Indicators. These dimensions include 1) target and outreach, 2) products and services, 3) benefits for the members and 4) social responsibility. The population of this study includes 38 VCI with total asset above Rp100 billion (> Rp 100 M) as the census technique was applied, all VCI was taken as the sample. The results show that the social performance of large VCI in Bali is very weak on target and outreach dimension but is strong on social responsibility. The pro-poor method and the individuals targeting are the weakest social performance criteria. These institutions must also focus their programs on helping the poor people. This can be done by collaborating with other institutions located in the areas with high poverty rates